Effective learning environments in higher education online settings : establishing social presence - Moroz, Karen, 1969-; Harvey, Trish; Carlson, Jennifer (Contemporary perspectives on learning environments, 2022)
"Effective online teaching is a well-documented topic, however, this book is different because it specifically addresses the effective and affective pedagogy and learning. It provides methods for building a strong and meaningful online environment that builds community, relationships, and establishes the social presence of each individual learner. This book provides a different perspective as it is written by experienced faculty members in higher education, all of whom have been teaching online for a decade or more. It also addresses the how and why establishing social presence as a necessity for effective online learning. This book addresses the "Why?" in the need for understanding contemporary approaches for exemplar online teaching with the establishment of social presence. With an increase in online learning, there is a shift in how current teaching practices are impacted and what is important to student learning in this change. This book describes the importance of strong andragogical practices in online teaching: rigor, teacher and learner mindset, and the importance of constructing social presence. Effective learning environments in higher education online settings: Establishing social presence provides pedagogical tools for enhancing the online learning experience. A relevant guide for constructing and teaching virtual/distance/elearning/online/hybrid/blended courses, faculty, instructional designers, professional development leaders, and administrators will find this book a practical and valuable resource for building community and establishing social presence in authentic ways"--